Teachers Turnover at Private Schools and its Impact on Teaching Learning: A study on Hetauda, Makawanpur, Nepal - Bhattarai, Rabi Kumar (Journal of Business and Social Sciences, 2024)
This research focuses on the Hetauda Sub-Metropolitan City in Makawanpur, Nepal, and examines the impact of teacher turnover on the teaching and learning process. Teacher turnover is a widespread issue in educational systems globally, and it can significantly affect student outcomes, school culture, and the overall quality of education. The study aims to understand the reasons behind the high teacher turnover rate among private schools in the region and analyzes its effects on teaching and learning. Using a mixed-methods approach that includes surveys and interviews the research identifies key factors contributing to teacher turnover and explores the implications for educational quality. The findings indicate that inadequate compensation, limited professional development opportunities, and poor working conditions are significant factors leading to high turnover rates. The study concludes with recommendations for improving teacher retention and enhancing the overall educational experience in private schools.